2010
DOI: 10.2136/sssaj2009.0029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of β‐Glucosidase Activity as a Soil Quality Indicator for the Soil Management Assessment Framework

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
1
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(219 citation statements)
references
References 42 publications
10
194
1
14
Order By: Relevance
“…The effect of cover crops on GLU/SOC ratio are in accordance with Stott et al (2010), who showed higher GLU/SOC ratios in soils with management systems that increased SOC content (for instance no-till soils or soils being converted to pasture) than in soils with management types characterized by SOC losses. The higher GLU/SOC ratios under both BV and CV cover crops would indicate that the new SOC incorporated into soil has a higher content of cellulosic substrates than the SOC present under CT.…”
Section: Discussionsupporting
confidence: 85%
“…The effect of cover crops on GLU/SOC ratio are in accordance with Stott et al (2010), who showed higher GLU/SOC ratios in soils with management systems that increased SOC content (for instance no-till soils or soils being converted to pasture) than in soils with management types characterized by SOC losses. The higher GLU/SOC ratios under both BV and CV cover crops would indicate that the new SOC incorporated into soil has a higher content of cellulosic substrates than the SOC present under CT.…”
Section: Discussionsupporting
confidence: 85%
“…Frequently recommended soil quality indicators include: soil organic matter (SOM), particulate organic matter (POM), microbial biomass carbon (MBC), potentially mineralizable nitrogen (PMN), macroaggregate stability, electrical conductivity (EC), sodium absorption ratio (SAR), pH, inorganic N, P, potassium (K), and magnesium (Mg), available water-holding capacity (AWC), bulk density (BD), topsoil depth, and infiltration rate [9,23,26]. Soil enzyme activity, specifically β-glucosidase activity which is involved in plant residue degradation, and water-filled pore-space were recently added to the recommended list of important soil quality indicators because of their association with soil biological properties and processes [27].…”
Section: Existing Soil Quality/health Assessmentmentioning
confidence: 99%
“…Assessment values are generally expressed as a fraction or percentage of full performance for soil functions such as crop productivity, nutrient cycling, or environmental filtering and buffering. Currently, the SMAF has scoring curves or interpretation algorithms for 13 indicators: water-stable macroaggregation (WSA), plantavailable water (PAW), water-filled pore space (WFPS), bulk density (BD), electrical conductivity (EC), pH, sodium adsorption ratio (SAR), extractable P and K, soil organic carbon (SOC), microbial biomass carbon (MBC), potentially mineralizable N (PMN), and b-glucosidase (BG) activity (Andrews et al, 2004;Wienhold et al, 2009;Stott et al, 2010).…”
Section: Introductionmentioning
confidence: 99%